Spotify resillience: scenario analysis of recession effects on Spotify industries - Barnes, Colton Grant (2021)
Spotify has only endured one recessionary cycle since inception in 2006 but was not public at the time so has yet to experience a market downturn during its stint as a listed company. With beta analysis only demonstrating a small factor of the company’s sensitivity to a recession, I will try and create an extensive scenario analysis with our model to illustrate valuation differences of Spotify in a possible recession scenario within the next 2-3 years. This will change revenue forecasts as well as costs forecasts, but with overall market performance decreasing during this period as well I will analyzethis scenarios impact on the growth of the streaming service industry within the entire music industry. How a possible recession in 2020/2021 will impact the cannibalization of the overall music industry by the streaming service transition, as well as discuss possible impacts to Spotify’s valuation in a recessionary case. As a tech company it is inherent that a recession will impact the valuation more than most companies, but this section will discuss by how much in and perform scenario analysis based on sizes of possible recessions to determine if Spotify would withstand even a large-scale market downturn as well as duration of possible recessions and Spotify’s resistance to these durations.